Frictional melting processes and the generation of shock veins in terrestrial impact structures: evidence from the Steen River impact structure, Alberta, Canada - Walton, Erin L. (My University, 2016)
Shock‐produced melt within crystalline basement rocks of the Steen River impact structure (SRIS) are observed as thin (1 – 510 μm wide), interlocking networks of dark veins which cut across and displace host rock minerals. Solid‐state phase transformations, such as ferro‐pargasite to an almandine‐andraditemajorite garnet and amorphization of quartz and feldspar, are observed in zones adjacent to comparatively wider (50─500 μm) sections of the shock veins. Shock pressure estimates based on the coupled substitution of Na+, Ti4+ and Si4+ for divalent cations, Al3+ and Cr3+ in garnet (14─19 GPa) and the pressure required for plagioclase (Ab62‐83) amorphization at elevated temperature (14−20 GPa) are not appreciably different from those recorded by deformation effects observed in non‐veined regions of the bulk rock (14─20 GPa). This spatial distribution is the result of an elevated temperature gradient experienced by host rock minerals in contact with larger volumes of impact‐generated melt and large deviatoric stresses experienced by minerals along vein margins.
Keywords: shock veins; Steen River impact structure; friction melting; majorite; shock metamorphism; high‐pressure phases; cratering; mechanics